Building Resilient Brokerage Systems : A Comprehensive Technical Guide - Raghu Danda (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article examines the critical aspects of building and maintaining resilient brokerage systems in today’s dynamic financial markets. The article explores the multifaceted challenges faced by modern trading platforms, from high-frequency trading demands to regulatory compliance requirements and market volatility management. It provides detailed insights into operational continuity strategies, including infrastructure redundancy and data management approaches, while addressing crucial cybersecurity frameworks and coding standards. The article demonstrates how advanced technologies, including artificial intelligence and machine learning, are revolutionizing trading system architectures and risk management capabilities. Through analysis of real-world implementations and industry best practices, this guide offers a holistic framework for establishing robust, secure, and highly available trading platforms that can withstand the demands of contemporary financial markets.